Pupillometry of Groove: Evidence for Noradrenergic Arousal in the Link Between Music and Movement - Bowling, Daniel L.; Graf Ancochea, Pablo; Hove, Michael J.; Fitch, W. Tecumseh (Frontiers in Neuroscience, 2019)
The capacity to entrain motor action to rhythmic auditory stimulation is highly developed in humans and extremely limited in our closest relatives. Investigating the mechanisms underlying this capacity thus represents an opportunity to advance our understanding of human evolution. An important aspect of auditory-motor entrainment is that not all forms of rhythmic stimulation motivate movement to the same degree. This variation is captured by the concept of musical groove: high-groove music stimulates a strong desire for movement, whereas low-groove music does not. Here, we utilize this difference to investigate the neurophysiological basis of our capacity for auditory-motor entrainment. In a series of three experiments we examine pupillary responses to musical stimuli varying in groove. Our results show stronger pupil dilation in response to (1) high- vs. low-groove music, (2) high vs. low spectral content, and (3) syncopated vs. straight drum patterns. We additionally report evidence for consistent sex differences in music-induced pupillary responses, with males exhibiting larger differences between responses, but females exhibiting stronger responses overall. These results imply that the biological link between movement and auditory rhythms in our species is supported by the capacity of high-groove music to stimulate arousal in the central and peripheral nervous system, presumably via highly conserved noradrenergic mechanisms.